(untitled) (Szociológiai Szemle, 2024)
The paper follows with attention the professional and political career of university professors and academicians, freshly joining the elite between 1945 and 1953. Merging the analysis of the historian, paying attention also to detail, with the technique of survey, it is shown how the points of selection of the new elite were changing during that brief period, how far the objectives of political cleansing were asserted, and what was the secret of remaining a member of the elite. The paper, utilising even the analysis of obituaries, closes with an attempt at setting up types of the learned elite.